Chronic effects of different exercise types on brain activity in healthy older adults and those with Parkinson’s disease: A systematic review - Wang, Leilei; Li, Feiyue; Tang, Lu (Frontiers in Physiology, 2022)
Objective: This study aimed to compare the regulation of brain activity by different kinds of long-term exercise (Tai Chi, treadmill training, and dancing) in healthy older adults and those with PD. Methods: From January 2000 to October 2021, the electronic databases PubMed, Web of Science, and Scopus were searched. All articles were screened throughout the inclusion and exclusion criteria, which was followed by PICOS criteria. Finally, all articles were systematically reviewed with analysis. Results: 29 studies were identified for this review, 24 of which were finally included in group of healthy older adults, and 5 of which in group of people with PD. All studies showed that significant changes were showed on people with PD and healthy older adults’ brain activity after three terms of exercise we chose. And an inverse change trend on functional connectivity in people with PD was observed after treadmill training, whereas an increased brain activity, cognitive function, memory, and emotion in healthy older adults. Conclusions: Our findings suggest that different patterns of brain activity were also observed between healthy older adults and people with PD after treadmill training. However, more robust evidence and comprehensive studies are needed to determine if there is a difference between the healthy older adults and people with PD.